Software educativo para la asignatura Estratificación de Riesgos Medioambientales. - de Jesús Cala Pérez, Manuel; Rodríguez Pérez, Ibis; Cala Hermosilla, Manuel Antonio; Garzón González, Elisdan (MEDISAN)
An investigation related to the technological innovation was carried out in the Health Nursing-Technology Faculty from Santiago de Cuba, during the school course 2019-2020, aimed at designing an educational software for the subject Stratification of Environmental Risks, directed to medium technician students in Surveillance and Vector Control. The theoretical methods used were: analysis-synthesis, historicallogical, modelation, systemic-structural and inductive-deductive; and the empiric methods were: observation and documental analysis. The sample had 44 students and 6 professors chosen at random. It was concluded that the proposed software is feasible, pertinent and necessary as teaching aid; provides up-to-date information, it is easy and interesting to surf internet, and allows the self-appraisal of students in the interaction with themselves, what contributes to improve the independent work.